Thriving in the academic domain: The role of career development on academic self-determined motivation - Patry, Danielle A (University of Ottawa (Canada), 2009)
The central purpose of the present research project was to examine the role of career development on academic motivation among adolescents. Based on self-determination theory (SDT; Deci & Ryan, 1985a) and future-oriented frameworks, it was hypothesized that two career development indices, namely career decision-making need satisfaction (i.e., competence, autonomy, and relatedness) and career decision progress would be associated with enhanced academic self-determined motivation. Second, perceived usefulness of school activities was expected to mediate the relationship between career decision progress and academic self-determined motivation. Third, the two career development indices were anticipated to contribute to perceived usefulness and academic self-determined motivation over and above the effect of academic need satisfaction. Four studies, using various methodologies and multiple age groups were conducted to test these hypotheses. Study 1 (n = 60) and Study 2 (n = 207) examined the role of career decision-making need satisfaction (i.e., competence exclusively) and career decision progress in the prediction of academic self-determined motivation. Using a two-wave longitudinal design, Study 1 showed that the career development indices contributed to variance in academic self-determined motivation over and above gender and baseline academic self-determined motivation. Using a pre-experimental design, Study 2 (i.e., pre-post career development course) demonstrated that an increase in the career development indices was associated with an increase in perceived usefulness and in academic self-determined motivation. Moreover, perceived usefulness mediated the relationship between career decision progress and academic self-determined motivation. Study 3a (n = 637) and Study 3b (n = 243) included satisfaction of all three needs postulated by SDT. Using a cross-sectional design (Study 3a) and a two-wave prospective design (Study 3b), findings showed that academic need satisfaction was associated with academic self-determined motivation, and that perceived usefulness partially mediated this relationship. Furthermore, Study 3b found that career decision-making need satisfaction and career decision progress contributed to variance in perceived usefulness and academic self-determined motivation, even after statistically controlling for academic need satisfaction. Together, these studies suggest that need satisfaction in both life domains and career decision progress enhance academic self-determined motivation. Future research pertaining to the role of career development on motivation is discussed.
Keywords: Psychology, General.